GENETIC EVALUATION OF LINEAR TYPE TRAITS AND THEIR ASSOCIATION WITH MILK PRODUCTION TRAITS IN BEETAL GOATS IN PAKISTAN - A. Waheed; M. S. Khan; E. Eyduran; M. A. Khan; A. Faraz; R. H. Mirza (Journal of Animal and Plant Sciences, 2019)
Data on linear type and milk production traits of Beetal does (n=127) were analyzed to estimate variance components hence genetic parameters and to find the relationship between linear type and milk production traits fitting an individual animal model. Fixed effects were flock and parity in the model while linear and quadratic effects ofage of doe were fitted as covariables. Genetic parameters (heritability estimates) of linear type traits and their correlations with milk production traits were computed using ASREML software. Heritability of various body measurement traits varied from 0.04 to 0.98. Genetic correlations between different body measurements and milk production traits ranged from -0.41 to 0.88 for lactation milk yield (LMY) and from -0.69 to 0.64 for lactation length (LL). Phenotypic correlations in corresponding combinations ranged from -0.33 to 0.90 for LMY, and from -0.46 to 0.89 for LL. In conclusion, some of thecorrelationscould provide strong effects in selection and prediction of milk production from linear type traits.
Keywords: Beetal goats; linear type traits; milk production; genetic parameters